Characterisation of Leptospira spp. and risk factors of leptospirosis in dogs diagnosed with kidney and/or liver disease - Abdul Rahman, Mohammad Sabri (2024)
Leptospirosis is a serious bacterial disease that affects both humans and animals. A wide range of symptoms have been reported in humans; the disease in dogs is commonly associated with kidney and/or liver disease. In Malaysia, information about the common serovars infecting dogs is limited. Therefore, this study investigated the occurrences of leptospirosis in 124 pet dogs diagnosed with kidney and/or liver disease and documented information such as signalment, medical history, management, and clinical findings. Altogether, 124 whole blood, 124 sera, 113 urine, four abdominal effusions, 23 kidneys and 23 livers were collected from the dogs. The samples were analysed using microscopic agglutination test (MAT), polymerase chain reaction (PCR) and histopathological methods [Hematoxylin and Eosin (H&E); Warthin Starry (WS) staining]. Statistical analyses were descriptively analysed, and risk analyses were performed using Pearson chi-square tests and logistic regression. This study evaluated TaqMan® real-time PCR (qPCR) assays, namely LipL32(1) and LipL32(2), used in the diagnosis of leptospirosis and investigated its applicability in clinical samples from dogs diagnosed with kidney and/or liver disease, in comparison with conventional PCR used as a reference. Based on MAT, 53 of 124 (42.7%) dogs were seropositive for leptospiral exposure. Sera were frequently positive for serovars Bataviae (n = 12), Javanica (n = 10), and Icterohaemorrhagiae (n = 10). Direct PCR detection showed that 42 of 124 (33.9%) of the whole blood and 36 of 113 (31.9%) urine samples were positive for pathogenic Leptospira spp. By PCR, 2 of 23 (9.1%) kidneys and 2 of 23 (9.1%) livers from four different dogs were positive for pathogenic Leptospira spp. Abdominal effusion from four dogs was PCRpositive for pathogenic Leptospira spp. The species detected were L. interrogans, L. borgpetersenii, L. kirschneri, and L. kmetyi by partial 16S rRNA sequencing. Eleven leptospiral isolates were successfully recovered from 8 dogs and were further identified and characterised as serovars Bataviae, Javanica, and Australis. In addition, the mortality rate of the Leptospirainfected dogs was high (18 of 53; 34%). Medium and large dog breeds with a history of exposure to rats and managed outdoors had a greater risk for leptospirosis (p = 0.045). The significant predictors for the dogs’ positivity were the presence of rats (p = 0.003) and acute clinical illness (p = 0.047). Administration of antibiotics (p = 0.036) and the detection of clinical illness at an early stage of the disease (p = 0.04) improved the survivability of the dogs. Identifying the profile of dogs at risk of eptospirosis could be helpful in the design of diagnostic and treatment strategies, as well as increasing awareness for the prevention of the disease. Results showed that the LipL32(1) qPCR assay was shown to have more diagnostic value than the LipL32(2) qPCR assay. Hence, the LipL32(1) qPCR assay was further analysed and revealed that the assay was able to detect DNA copies as low as 5 per reaction with high specificity against the tested leptospiral strains. No cross-amplification was observed with the other organisms. During the investigation using the clinical samples, the LipL32(1) qPCR assay had 100.0% sensitivity and more than 75.0% specificity. This suggested that the LipL32(1) qPCR assay is sensitive, specific and has the potential to be applied in a more extensive subsequent study. The canine kidneys and livers of the Leptospira-infected dogs (n = 18) showed relevant histopathological lesions of canine leptospirosis, consisting of interstitial nephritis, glomerular atrophy and tubular necrosis and varying degrees of vascular and degenerative changes with scattered areas of mononuclear cell infiltration in the liver. Using WS staining, spirochete organisms were also found in the kidneys (n = 3) and livers (n = 2). Histopathology assessment of tissue samples is essential for a definitive diagnosis of the lesions and antigen demonstration that could support the evidence of canine leptospirosis. This study has shown that at least 1 in 3 dogs with kidney and/or liver disease in Malaysia can potentially have leptospirosis. Veterinarians examining dogs with these conditions should consider leptospirosis as a differential diagnosis. Furthermore, the isolation of serovars Bataviae, Javanica, and Australis is essential, given their absence in commercial vaccines. Therefore, proper characterisation of leptospiral isolates is critical for providing evidence-based knowledge to support developing and commercialising multivalent vaccines containing serovars circulating among local populations.